Ablative thermal protection systems modeling - Duffa, Georges (AIAA education series., 2013)
This book explains the history of ablative materials and looks into the future of its design process. Topics include: modeling based on small physics scales; thermodynamics and transport properties; gas kinetics; radiative transfer; physical and chemical reactions (homogeneous and heterogeneous); fluid mechanics and effects of turbulence on physical matter; transport properties approximation; equilibrium thermodynamics in variable elemental medium; ablation of glassy materials; roughness setup and effects; and radiative transfer in materials. The objective of this book is to develop physical skills in the key scientific areas applied to the modeling of thermal protection. --